Influence of integrated crop-livestock-forest on morphological composition and nutritional value of Marandu palisadegrass under continuous grazing - de Santana, Erikelly Aline Ribeiro [UNESP]; Costa, Ciniro [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; Andrighetto, Cristiana [UNESP]; Mateus, Gustavo Pavan; da Luz, Patrícia Aparecida [UNESP]; Aranha, Aline Sampaio [UNESP]; Lupatini, Gelci Carlos [UNESP]; Fialho, Cleunice Auxiliadora [UNESP]; Aranha, Helena Sampaio [UNESP] (Universidade Estadual de Londrina, 2021)
This study characterizes the changes in leaf mass, morphological composition and nutritional value of leaf blades of palisadegrass (Urochloa brizantha cv. Marandu) under continuous grazing in the first year of implementation of pasture and after second year of the eucalyptus planting in an Integrated Crop-Livestock System and Integrated Crop-Livestock-Forest, which were tested in the four seasons. The experimental design was in random blocks, with three treatments: Crop-Livestock System (ICL) and Integrated Crop-Livestock-Forest with two eucalyptus tree densities (ICLF-1L, 196 eucalyptus trees ha-1 and ICLF-3L, 448 eucalyptus trees ha-1) and four replicates. Sixty castrated Nellore cattle with initial weight of 235.43 ± 25.46 kg and mean age of 16 ± 2.81 months were used during the growing phase under continuous grazing. The agronomic variables were: total dry mass of forage, leaves, stem and dead material; leaf: stem and live: senescent material ratios; and accumulation rate. The leaf: stem and live: senescent material relation did not obtain any difference between the evaluated systems. Dry matter, crude protein, fiber fractions and digestibility of leaf blades were evaluated. Dry mass of the forage (6775 kg ha-1), stem (2175 kg ha-1), senescent material (3175 kg ha-1) and dry matter content (28.6%) were greater in the ICL, whereas crude protein (11.3%) was greater in the ICLFs. On the other hand, accumulation rate and dry mass of leaf blades did not change between systems. Thus, until the first year of grazing, tree systems have advantages, because the forage production (accumulation rate) and leaf mass are similar to those of plants in full sun, besides showing higher nutritional value.
Influência da integração lavoura-pecuária-floresta na composição morfológica e valor nutricional do capim-marandu sob pastejo contínuo
Keywords: Digestibility; Leaf: stem ratio; Morphological composition; Urochloa brizantha